Four delays of child mortality in Rwanda: a mixed methods analysis of verbal social autopsies. Issue 5 (27th May 2019) - Roder-DeWan, Sanam; Gupta, Neil; Kagabo, Daniel M; Habumugisha, Lameck; Nahimana, Evrard; Mugeni, Catherine; Bucyana, Tatien; Hirschhorn, Lisa R
Abstract : Objectives: We sought to understand healthcare-seeking patterns and delays in obtaining effective treatment for rural Rwandan children aged 1–5 years by analysing verbal and social autopsies (VSA). Factors in the home, related to transport and to quality of care in the formal health sector (FHS) were thought to contribute to delays. Design: We collected quantitative and qualitative cross-sectional data using the validated 2012 WHO VSA tool. Descriptive statistics were performed. We inductively and deductively coded narratives using the three delays model, conducted thematic content analysis and used convergent mixed methods to synthesise findings. Setting: The study took place in the catchment areas of two rural district hospitals in Rwanda—Kirehe and Southern Kayonza. Participants were caregivers of children aged 1–5 years who died in our study area between March 2013 and February 2014. Results: We analysed 77 VSAs. Although 74% of children (n=57) had contact with the FHS before dying, most (59%, n=45) died at home. Many caregivers (44%, n=34) considered using traditional medicine and 23 (33%) actually did. Qualitative themes reflected difficulty recognising the need for care, the importance of traditional medicine, especially for 'poisoning' and poor perceived quality of care. We identified an additional delay—phase IV—which occurred after leaving formal healthcare facilities. These delays were associated with caregiver dissatisfaction or inability to adhere to care plans. Conclusion: Delays in deciding to seek care (phase I) and receiving quality care in FHS (phase III) dominated these narratives; delays in reaching a facility (phase II) were rarely discussed. An unwillingness or inability toadhere to treatment plans after leaving facilities (phase IV) were an important additional delay. Improving quality of care, especially provider capacity to communicate danger signs/treatment plans and promote adherence in the presence of alternative explanatory models informed by traditional medicine, could help prevent childhood deaths.